2014
DOI: 10.1007/s00213-014-3795-8
|View full text |Cite
|
Sign up to set email alerts
|

fNIRS suggests increased effort during executive access in ecstasy polydrug users

Abstract: Background: Ecstasy use is associated with cognitive impairment, believed to result from damage to 5-HT axons. Neuroimaging techniques to investigate executive dysfunction in ecstasy users provide a more sensitive measure of cognitive impairment than behavioural indicators. The present study assessed executive access to semantic memory in ecstasy polydrug users and nonusers. Methods: Twenty ecstasy polydrug users and 20 non-user controls completed an oral variant of the Chicago Word Fluency Test (CWFT), whilst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Indices of ecstasy use were significantly associated with all changes in cortical haemodynamics, frequency of use with RPFC oxygenation change and LPFC and RPFC deoxygenation change, lifetime dose with RPFC deoxygenation change, and recent use with all significant haemodynamic changes. This is in line with recent studies from our own lab where recency of use was a significant predictor of oxy-Hb change during an inhibition task (Roberts & Montgomery, 2015a) and a semantic access task (Roberts & Montgomery, 2015b).…”
Section: Inspection Ofsupporting
confidence: 92%
“…Indices of ecstasy use were significantly associated with all changes in cortical haemodynamics, frequency of use with RPFC oxygenation change and LPFC and RPFC deoxygenation change, lifetime dose with RPFC deoxygenation change, and recent use with all significant haemodynamic changes. This is in line with recent studies from our own lab where recency of use was a significant predictor of oxy-Hb change during an inhibition task (Roberts & Montgomery, 2015a) and a semantic access task (Roberts & Montgomery, 2015b).…”
Section: Inspection Ofsupporting
confidence: 92%
“…Previous fNIRS studies have investigated DLPFC contribution to several processes cognitive, such as word-encoding in a memory task (Ferreri et al, 2014), inhibitory control in drug users (Roberts & Montgomery, 2015), dual motor and cognitive task-performance (Mandrick et al, 2013). Relevant to the current results, two studies targeted hemodynamic responses in DLPFC in effortful tasks, specifically testing the effect of varying mental load in a working memory task (Molteni et al, 2012), and comparing laboratory measures of load (executive function task) with real-life effort (operating a flight-simulator Causse et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased pre-synaptic SERT and increased post-synaptic 5-HT 2A receptor availability are consistent with serotonin axon damage. Moreover, functional neuroimaging studies have observed ecstasy-related adjustments to cerebral blood flow in frontal areas, with functional near-infrared spectroscopy (Roberts & Montgomery, 2015 a ) and fMRI (Moeller et al 2004 ; Jager et al 2008 ; Roberts & Garavan, 2010 ). It is noteworthy that all of the functional imaging studies mentioned observe increased neuronal activity to achieve similar behavioural performance to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Several neuroimaging studies have concluded that ecstasy-related neuronal adaptations may occur neurophysiologically before they manifest functionally. Roberts & Montgomery ( 2015 a ) suggested that ecstasy users display increased blood flow to areas of the PFC during a verbal fluency task, despite no differences in task performance. This suggests that ecstasy users work harder to achieve similar performance to controls, and that functional differences may be apparent with increased workload.…”
Section: Introductionmentioning
confidence: 99%